Healthcare security in edge-fog-cloud environment using blockchain: A systematic review - Al-Araji, Zaid Jasim; Hazem Al-Sheikh, Najwa N.; Ibrahim Al-Dulaimi, Abdullah A.; Yassen, Ayad; Hikmat, Namaa N.; Syed Ahmad, Sharifah Sakinah; M. Farhood, Hussein; Abdulkadhim, Zaid Ali; Mutlag, Ammar Awad; Alkhaldee, Mahmood S.; Hashim Ali, Ammar (Mesopotamian Academic Press, 2025)
Context: Our domain of expertise is healthcare security, which protects the sensitive information of patients and the integrity of the healthcare services provided to them. As health record digitization grows, along with the adoption of advanced technologies, data protection becomes more complex and vital. Realizing the transformative potential of blockchain (BC) in healthcare security requires critical exploration into the prevailing centralization of sensitive patient information, shedding traditional paradigms, and embracing the digital decentralization enabled by the BC realm. Objectives: The purpose of this study was to analyse prior research and provide a comprehensive overview of the literature on BC-based healthcare security in edge-fog-cloud (EFC) scenarios. Face and researchers, outlining the obstacles they face and offering recommendations to analysts for enhancing this crucial area of study. Methods: The analyses systematically examined healthcare security utilizing BC within the EFC domain across all studies; additionally, four databases—Web of Science (WoS), ScienceDirect, IEEE Xplore Digital Library, and Scopus—were employed from 2019--2024 to analyse their architecture, applications, and performance evaluation. Results: In accordance with our inclusion and exclusion criteria, 97 publications concerning healthcare security utilizing BC in edge, fog, and cloud systems with various approaches and strategies were chosen. Four classes were created from the taxonomy results according to the BC location: healthcare security using BC at the edge, healthcare security using BC in fog, healthcare security using BC in the cloud, and review articles. Discussion: BC facilitates secure and efficient sharing of patient data among different healthcare systems, promoting seamless interoperability of electronic health records (EHRs). Data are also stored in a decentralized manner, which diminishes the danger of breaches because there is no singular point of failure. Additionally, with national tracking protocols via BC, full lifecycle monitoring of pharmaceutical products is ensured, guaranteeing transparency and minimizing counterfeit medication. Conclusion: Although the research domains of healthcare security using BC in EFC differ, they are generally equally important. Through this review, research capabilities are highlighted, and new research domains are expanded.